Design and evaluation of lidocaine- and prilocaine-coloaded nanoparticulate drug delivery systems for topical anesthetic analgesic therapy: a comparison between solid lipid nanoparticles and nanostructured lipid carriers - You P; Yuan R; Chen C (Dove Medical Press, 2017)
Peijun You,1 Ran Yuan,2 Chuanyu Chen1 1Department of Anesthesiology, Shandong Jining No 1 People’s Hospital, Shandong, People’s Republic of China; 2Department of Anesthesiology, Affiliated Hospital of Jining Medical College, Jining, Shandong, People’s Republic of China Purpose: Topical anesthesia analgesic therapy has diverse applicability in solving the barrier properties of skin and unfavorable physicochemical properties of drugs. Lidocaine (LID) combined with prilocaine (PRI) has been used as a topical preparation for dermal anesthesia for treatment of conditions such as paresthesia. Materials and methods: In this study, for combination anesthesia and overcoming the drawbacks of LID and PRI, respectively, LID- and PRI-loaded solid lipid nanoparticles (SLNs) and nanostructured lipid carriers (NLCs) were prepared and characterized by determination of their particle size, drug loading capacity, stability, in vitro drug release behavior and in vitro cellular viability. Ex vivo skin permeation and in vivo anesthesia analgesic efficiency of these two systems were also evaluated and compared. Results: Results revealed that combination delivery of the dual drugs exhibited more remarkable efficiency than signal drug-loaded systems. SLN systems have better ex vivo skin permeation ability than NLCs. NLC systems revealed a stronger in vivo anesthesia analgesic effect than SLN systems. Conclusion: It can be concluded that SLNs and NLCs have different advantages, and that both carriers are promising dual drug delivery systems for topical anesthetic analgesic therapy. Keywords: topical anesthesia, prilocaine, lidocaine, solid lipid nanoparticles, nanostructured lipid carriers